Analysis of Amplitude Modulation Using labVIEW - Sharma, Nipun; Sharma, Palkin (International Journal of Computer Sciences and Engineering, 2025)
Analog Communication techniques based on modulation of carrier signal are used from years ago and still they are widely used. Amplitude Modulation is one of them. In this paper we had done simulative investigation on effect of modulation index on AM Wave using LabVIEW software.Various cases are being discussed showing effect of modulation index on shape of AM .These different shapes of AM wave have many uses in communication. Power Spectral Density is also calculated also showing effect of modulation index on sideband power. Power Spectral density specifies relationship between power ,modulation index and carrier frequency.